Peningkatan kemampuan koneksi matematik peserta didik menggunakan model problem based learning (PBL) dengan berbantuan Software Geogebra - Linda Herawati (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2017)
This study aims to determine the improvement of mathematical connection ability of students using Problem Based Learning model (PBL) with GeoGebra assisted software and not assisted GeoGebra software. The research method used is the experimental method with the population of all students classes VII SMP Negeri 1 Rajapolah. Samples were taken two classes at random, selected class VII-I using Problem-Based Learning model with GeoGebra software and class VII-H using Problem Based Learning model. Data collection techniques in this study are to test the ability of mathematical connections of learners and disseminate the questionnaire of mathematical disposition. Instruments used in this study is a matter of test the ability of mathematical connections of learners. Data analysis technique used is the test of difference of two mean and quantitative descriptive analysis. Based on the results of processing, data analysis and hypothesis testing obtained the conclusion that the improvement of mathematical connection ability of learners through Problem Based Learning (PBL) model of GeoGebra software is not better or same with Problem Based Learning (PBL) model which is not supported by GeoGebra software.